Modifikasi Alternator dan Sistem Kelistrikan Untuk Peningkatan Daya Listrik Sepeda Motor 125 cc - Alfi Tranggono Agus Salim; Eko Darmawan; Yoga Ahdiat Fakhrudi; Izhary Siregar; Balkhaya Balkhaya; Muhammad Anhar Pulungan; Sufiyanto Sufiyanto; Thenny Daus Salamoni (Jurnal Energi dan Teknologi Manufaktur, 2019)
The alternator on the motor is one component of the vehicle that can be used to improve its utilization. Modifications to the alternator on the vehicle are made to increase electric power. The working principle of an electric generator is in accordance with the law of faraday if a conductor is rotated in a magnetic field until it crosses the magnetic force line (GGM), it will cause an electric force line (GGL) in volts at the end of the conductor. In the alternator to be used, the lighting coil resistance is 0.24 - 0.36 Ω and the charging is 12.3 - 13.3 V at 1500 rpm. The research conducted was an experiment by comparing the alternator output voltage before it was modified with the alternator output that had been modified. Modification of the alternator is done by the method of load variation and replacement of the diameter of the coil along with the number of turns on the alternator. Measurement of alternator before and after modification shows results that are directly proportional to the output of the alternator at 1,000 rpm - 8,000 rpm. The results of three tests can be concluded that the modification of the alternator has increased from 6.42 A for the standard alternator to 13.7 A for the modification alternator.